Will Indonesia Surpass Malaysia in SGIE? - Siregar, Fitri Susanti; MA, DR. Sugianto (ITB AAS INDONESIA Surakarta, 2024)
Based on the 2023 State of the Global Islamic Economy (SGIE) report, Indonesia managed to enter the top three in the Global Islamic Economy Indicator (GIEI) released by DinarStandard in Dubai, United Arab Emirates, Tuesday (26/12/2023). Indonesia, which will be in fourth place in 2022, is now in third place, below Malaysia, which has consistently been in first place for the last 10 years. As a Muslim-majority country with abundant resource potential, Indonesia should be ranked higher than Malaysia, Saudi Arabia and the United Arab Emirates in the SGIE ranking report. This shows that there is still a large gap between potential and expectations, so it is interesting to research considering that Indonesia is the country with the largest Muslim population in the world, surpassing Malaysia with the percentage of the Muslim population reaching 87.20% of the total population of 273.5 million people. This research uses a qualitative descriptive method by collecting several journals and annual reports regarding the Global Islamic Economy. This research discusses what strategies the Indonesian government can implement to develop the halal industrial sector so that Indonesia can surpass Malaysia in dominating the halal industry in the world.